Persaingan Antarnegara dalam Pariwisata Internasional: Analisis Pengaruh dan Klusterisasi Daya Saing - Fahmi Tarumanegara; Fitri Juliana Sanjaya; Muh. Asy'ari (Universitas Bosowa, 2026)
Tourism has become one of the key industries contributing to the global economy. Interestingly, countries endowed with abundant tourism resources are not necessarily those that derive the greatest benefits from this sector. This study examines the influence of tourism competitiveness on the Human Development Index (HDI), Sustainable Development Goals (SDGs) achievement, and Gross National Income (GNI) per capita, while also exploring the dynamics of international tourism competition. An explanatory quantitative approach was employed using multiple linear regression and K-Means cluster analysis. The study utilized data from 117 countries obtained from the Travel and Tourism Development Index (TTDI) published by the World Economic Forum (WEF). The findings reveal that, simultaneously, all dimensions of tourism competitiveness have a significant effect on HDI, SDG achievement, and GNI per capita. However, the magnitude and significance of these effects vary across dimensions when examined individually. Notably, the demand drivers dimension, which represents tourism resources, does not exert a significant influence on any of the economic indicators. The cluster analysis further identifies four groups of countries by distinct competitiveness characteristics and differing patterns of competition. Amid increasingly intense competition in the global tourism industry, countries need to continuously strengthen their tourism competitiveness. Such competitiveness can no longer rely solely on the abundance of natural and cultural resources but must increasingly be driven by the creation of a supportive enabling environment, the development and improvement of infrastructure, and effective policy governance aligned with national development objectives.